REDUCTION IN FLOATING PLATFORM RESPONSES CONSIDERING SHORT-CRESTEDNESS OF W A YES - NG , CHENG YEE (2014)
Spar and semi-submersible platforms are the common types of large lloating offshore platforms operating in deepwater region. Due to lack of sufficient analytical, experimental and statistical data regarding the regarding the performances of these platforms subjected to the real sea condition of short-crested waves, these platforms are normally designed for long-crested waves. In the real sea condition, only shortcrested waves are found. The short-crested waves are defined as linear summation of long-crested waves propagated in dit1erent directions. The wave forces generated would be randomly varying in the magnitude and direction. In the literature, very tew numerical and experimental studies have been reported about the dynamic responses of spar and semi-submersible platforms subjected to short-crested waves.